2007
DOI: 10.1016/j.neuropharm.2006.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Sensitization to the conditioned rewarding effects of morphine modulates gene expression in rat hippocampus

Abstract: Opiates addiction is characterized by its long-term persistence. In order to study the enduring changes in long-term memory in hippocampus, a pivotal region for this process, we used suppression subtractive hybridization to compare hippocampal gene expression in morphine and saline-treated rats. Animals were subjected to an extended place preference paradigm consisting of four conditioning phases. Sensitization to the reinforcing effects of the drug occurred after three conditioning phases. After 25 days of tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…Considering the critical role of SNAP25 in exocytosis and regulating neural plasticity (60 -62), SIP30 is likely involved in mediating long term pain plasticity and LTP. This hypothesis is in agreement with a recent paper in which SIP30 was identified as a long term memory consolidation associated gene in opiate addiction (63). Furthermore, SIP30 would be probably located in spinal excitatory interneurons to enhance neuron excitability, as hippocampal GABAergic inhibitory synapses lack SNAP-25 (64, 65).…”
Section: Discussionsupporting
confidence: 91%
“…Considering the critical role of SNAP25 in exocytosis and regulating neural plasticity (60 -62), SIP30 is likely involved in mediating long term pain plasticity and LTP. This hypothesis is in agreement with a recent paper in which SIP30 was identified as a long term memory consolidation associated gene in opiate addiction (63). Furthermore, SIP30 would be probably located in spinal excitatory interneurons to enhance neuron excitability, as hippocampal GABAergic inhibitory synapses lack SNAP-25 (64, 65).…”
Section: Discussionsupporting
confidence: 91%
“…Similarly, training in conditioned place preference for amphetamine increased c-fos expression in the hippocampus of rats [207]. Furthermore, extended training in a morphine-conditioned place preference paradigm altered gene expression in the hippocampus of rats [208]. Changes in gene expression are not limited to laboratory animals.…”
Section: Nicotine Contextual Learning and Addictionmentioning
confidence: 99%
“…One such study, which involved morphine-induced conditioned place preference, showed changes in the expression of genes in the hippocampus involved in vesicular transport, neurotransmitter release, and receptor trafficking (Marie-Claire et al, 2007). However, there are few studies detailing the effects of prescription opioids on changes in gene expression in the adolescent brain (Ellgren et al, 2007).…”
Section: Introductionmentioning
confidence: 99%